ANALISIS PERILAKU KARYAWAN MUSLIM DI BENGKULU UTARA YANG TERDAMPAK COVID-19 - Debby Arisandi (KOMPLEKSITAS: JURNAL ILMIAH MANAJEMEN, ORGANISASI DAN BISNIS, 2021)
The purpose of this study was to find out what behaviors and negative impacts occurred on Muslim employees who were affected by Covid-19 in North Bengkulu. The type of research is descriptive qualitative by conducting field research. The results of the research found that: 1) The behavior of Muslim employees has full responsibility for their work. For them, an employee must have a sense of responsibility towards work, be trustworthy, disciplined, positive thinking, empathetic and professional. 2) The behavior of Muslim employees affected by Covid-19 is innovative, namely creating new ideas for doing their work. This Covid has indeed had an impact on employees, employees present solutions that have not been shown by others in overcoming this problem, such as looking for a side job to fulfill their daily needs.